Analisis Perbandingan Produktifitas dan Efsiensi Pengiriman Material pada Sistem Aging dan Sistem Scheduling Route Menggunakan Analisis Produktifitas dan Data Envelopment Analysis (DEA) - Indro Prakoso; M Baharuddin Wahit Tosaili; Tigar Putri Adhiana (SPECTA Journal of Technology, 2021)
Productivity and efficiency are two main things that can be used as benchmarks for success from the Delivery section of the SCM department. Productivity is the main point in assessing whether the Delivery system in the warehouse is feasible or has not reached its target. In the last few periods after carrying out a track record of the historical data of the shipment of goods. It was found that in one week there were frequent deliveries to the same user drop point location, meaning that this could lead to waste & waste from inefficient work. In connection with that, a new system is implemented, the scheduling system, which is a delivery system for delivering material with a predetermined schedule every week. This research is intended to produce a productivity analysis that shows whether this new scheduling system can increase productivity and delivery efficiency when compared to an aging system or vice versa by using a productivity analysis methodology and efficiency level benchmarking using data envelopment analysis (DEA). The results of the aging system productivity analysis have a better value, namely 34%, while the scheduling system is 26%, but scheduling has a shorter distance so it can make savings. Meanwhile, in comparison to efficiency using benchmark factors, it is found that the aging system is more efficient with an optimum value of 1, and scheduling of 0.9855535 is considered inefficient.